Miller's Crossing [videorecording (DVD)] - Coen, Joel; Coen, Ethan; Byrne, Gabriel, 1950-; Harden, Marcia Gay; Turturro, John, 1957- (Twentieth Century Fox Home Entertainment ; Fox Video, 2003)
During prohibition two gangland bosses struggle for control over a city, with one of the boss's lieutenants caught in the middle.